Фигурное украшение первых веков н. э. из раскопок Портового района Херсонеса - Нессель, В. А. (Давнина. Харківський історико-археологічний щорічник, 2016)
Summary V. Nessel. The figurian jewel of the firsts centuries AD from the Port area of Chersonesos This paper deals with the miniature figurine made from so-called Egyptian faience, which was found in site of medieval house in the Port area of Chersonesos during the excavation 1991. The mouldmade figurine is produced from fine-grained paste of yellow-green tone. It measures: 23 mm — in height, 11 mm- in maximal width of base. According to well-known analogies this find dates to the 1sts centuries AD. The figurine represents the woman in a high headdress, sitting on a throne. The typical details promoting exact attribute of this find were not kept. Such position of a female figurine on a throne is typical for many antique goddesses but a presence of a kalathos or polos pulls it with Cybele and Isis. These eastern cults else were known in the Northern Black Sea coast in the Hellenistic period, and during the Roman time they were the most popular. The assumption that in our case the faïпence figurine shows a universal image of the Goddess-Mother is given in the paper. Similar miniature figurines are used as amulets and have been widespread in all parts of ancient world.